The Influence of Industrial Relations on Employee Work Motivation in Improving Organizational Performance - Chalisa Mahany; Marzuti Isra; Suhendri Suhendri; Purjianto Purjianto; Adi Amin Putra; Bayu Rizki Ananda; Dimas Abang Priatama; Muhammad Dwi Nanda; Rahmat Sarif (Lembaga Pengembangan Kinerja Dosen, 2026)
This material examines the dynamics of industrial relations as a fundamental framework for fostering positive and sustainable collaboration among workers, management, and government institutions within organizational settings. The discussion focuses on the role and function of labor unions, the core principles of industrial relations, and their alignment with labor regulations that define the rights, obligations, and responsibilities of all stakeholders. In addition, the material highlights the importance of implementing Occupational Safety and Health (OSH) through systematic risk assessment, hazard control, and comprehensive safety programs aimed at creating a safe, healthy, and efficient working environment. The study also explores motivational and behavioral aspects in the workplace by reviewing major motivation theories, key factors influencing employee motivation, and practical strategies organizations can adopt to enhance work motivation and engagement. Overall, this material emphasizes that harmonious industrial relations, effective OSH implementation, and well-managed employee motivation are interrelated components that play a critical role in increasing organizational productivity, improving employee performance, and ensuring long-term organizational sustainability.